The influence of temperature on the behavior of burrowing in larvae of the blowflies, Chrysomya albiceps and Lucilia cuprina, under controlled conditions - Gomes, Leonardo [UNESP]; Gomes, Guilherme [UNESP]; Von Zuben, Claudio J. (Oxford University Press (OUP), 2009)
Blowflies use discrete, ephemeral substrates for larval development. After exhaustion of the food supply, larvae will disperse in search of sites to burrow and pupate or will seek other sources of food in a process known as post-feeding larval dispersal. In this study, the effect of temperature was investigated as it is one of the most important aspects of the environmental variables in this process. 800 larvae of the blowflies Chrysomya albiceps (Wiedemann 1819) and Lucilia cuprina (Wiedemann 1830) (Diptera: Calliphoridae) were incubated in tubes covered with vermiculite at 15, 20, 25 and 30°C. For each pupa, the body weight, sex and depth of burrowing were determined. Statistical tests were used to examine the relationship of depth of burrowing and body weight to the temperature at which burrowing occurred. Depth of burrowing was affected differently by temperature for both of the species studied; L. cuprina larvae burrowed deeper at lower and higher temperatures while C. albiceps larvae burrowed less at extreme temperatures. Additionally, temperature had a significant effect on the body weight of L. cuprina larvae as body weight decreased as temperature increased, whereas for C. albiceps, pupal weight increased up to 25°C and then decreased abruptly at a higher temperatures. The maximum body weight was also differently affected in the two species; in L. cuprina, the maximal weight was at 15°C and for C. albiceps weight was maximal at 20°C. Copyright: This is an open access paper. We use the Creative Commons Attribution 3.0 license that permits unrestricted use, provided that the paper is properly attributed.
Keywords: Blowflies; Burrowing behavior; Larval dispersal; Temperature